2016
DOI: 10.1371/journal.pone.0147301
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Glucose Sensitivity and Stability of Trichoderma reesei β-Glucosidase Using Site-Directed Mutagenesis

Abstract: Glucose sensitivity and pH and thermal stabilities of Trichoderma reesei Cel1A (Bgl II) were improved by site-directed mutagenesis of only two amino acid residues (L167W or P172L) at the entrance of the active site. The Cel1A mutant showed high glucose tolerance (50% of inhibitory concentration = 650 mM), glucose stimulation (2.0 fold at 50 mM glucose), and enhanced specific activity (2.4-fold) compared with those of the wild-type Cel1A. Furthermore, the mutant enzyme showed stability at a wide pH range of 4.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…At low substrate concentrations, the velocity increases with increasing substrate concentration but starts to decrease when substrate concentration exceeds a certain optimum concentration. The activation of BGs that show substrate inhibition (i.e., non Michaelis–Menten kinetics) by inhibitor has also reported [32, 38]. Therefore, we were curious whether the competition of inhibitor with the nonproductive binding of substrate can result in the activation of enzyme also in the presence of substrate inhibition.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…At low substrate concentrations, the velocity increases with increasing substrate concentration but starts to decrease when substrate concentration exceeds a certain optimum concentration. The activation of BGs that show substrate inhibition (i.e., non Michaelis–Menten kinetics) by inhibitor has also reported [32, 38]. Therefore, we were curious whether the competition of inhibitor with the nonproductive binding of substrate can result in the activation of enzyme also in the presence of substrate inhibition.…”
Section: Resultsmentioning
confidence: 97%
“…This phenomenon has been often reported with the inhibition of BGs by glucose [11–36], and xylose [13, 15, 19, 21, 22, 2831, 37], but also by other sugars [19, 28, 31]. With some of these BGs, the Michaelis–Menten saturation kinetics holds [19, 21, 26, 31], with others, it does not [32, 38]. Most common mechanistic interpretations of the activation by inhibitor include transglycosylation to inhibitor [19, 26] and binding of inhibitor to an allosteric regulatory binding site [21, 39], whereas the glucose tolerance has been explained by the deep and narrow active site architecture of GH1 BGs [40].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Understanding the mechanism of glucose inhibition/tolerance is of crucial importance for biofuel production. Recently, replacement of two amino acids (Leu 167 and Pro 172) at the entrance of the active site of intracellular β-glucosidase of T. reesei (Bgl II) with Trp and Leu, respectively, significantly enhanced glucose tolerance e.g., Ki of 650 mM [141]. Further studies for identification of new β-glucosidase with high glucose tolerance are required.…”
Section: Glucose Sensitivity and Tolerancementioning
confidence: 99%
“…Drobecq et al changed the cysteine residue to alanine in small ubiquitin-like modifiers to improve their thermo-stability [17]. Several other papers have also reported that site-directed mutagenesis (replacing an amino acid with another) of enzymes enhanced heat stability [21,22]. To ensure the rigid structure of enzymes, the simplest way is to introduce a disulfide-bond at an internal chain of proteins [17][18][19][20][21][22][23].…”
Section: Strategy For Enhancing Heat Stabilitymentioning
confidence: 99%